Wetting Transitions: Counterintuitive Wetting Transitions in Doubly Reentrant Cavities as a Function of Surface Make‐Up, Hydrostatic Pressure, and Cavity Aspect Ratio (Adv. Mater. Interfaces 22/2020). Issue 22 (20th November 2020) - Arunachalam, Sankara; Ahmad, Zain; Das, Ratul; Mishra, Himanshu
Abstract : In article number 2001268, Himanshu Mishra and co‐workers present a comprehensive report on the strengths and weaknesses of biomimetic doubly reentrant cavities in the context of pressure‐induced wetting transitions underwater. They pinpoint the contributions of surface make‐up, hydrostatic pressure, and cavity profile and aspect ratio through a broad set of experimental techniques and mathematical modeling.